2020
DOI: 10.1021/acs.analchem.0c00912
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Multimodal Analytical Approach by Integrating Raman Optical Tweezers and RNA Sequencing

Abstract: Single-cell analysis has become a state-of-art approach to heterogeneity profiling in tumor cells. Herein, we realize a kind of single-cell multimodal analytical approach by combining single-cell RNA sequencing (scRNA-seq) with Raman optical tweezers (ROT), a label-free single-cell identification and isolation technique, and apply it to investigate drug sensitivity. The drug sensitivity of human BGC823 gastric cancer cells toward different drugs, paclitaxel and sodium dichloroacetate, was distinguished in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…16 Furthermore, extensive studies demonstrated successful classification in cancerous cells based on LTRS where the signals were mainly originated from DNA-RNA and proteins. [17][18][19] These results showed that the LTRS system has great potential to be a novel, convenient, and powerful tool for cell sorting and intracellular dynamics monitoring. However, whether LTRS could accurately discriminate drug sensitive and resistant cells remain unknown.…”
Section: Introductionmentioning
confidence: 81%
“…16 Furthermore, extensive studies demonstrated successful classification in cancerous cells based on LTRS where the signals were mainly originated from DNA-RNA and proteins. [17][18][19] These results showed that the LTRS system has great potential to be a novel, convenient, and powerful tool for cell sorting and intracellular dynamics monitoring. However, whether LTRS could accurately discriminate drug sensitive and resistant cells remain unknown.…”
Section: Introductionmentioning
confidence: 81%
“…These methods can be combined with fluorescence in situ hybridization (FISH) using rRNA-targeted probes 13 , enabling a direct link between function and identity of the organisms. In addition, recently Raman-activated cell sorting has been developed, using either optical tweezers or cell ejection for downstream sequencing of the sorted cells [14][15][16] . While these approaches have expanded the possibilities for functional analyses of microbiome members 17 , all of the aforementioned methods suffer from extremely limited throughput.…”
Section: Mainmentioning
confidence: 99%
“…Raman spectroscopy is a label-free, rapid, and highly sensitive analytical technology [4][5][6][7], and in recent years, it has been used to identify bacteria [6,[8][9][10]. In various Raman technologies, surface-enhanced Raman spectroscopy (SERS) is a commonly used tool for bacterial analysis, which has been widely used in bacterial cell cycle monitoring [11], drug resistance [12], and identification [4,8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%